New Media and Religious Conversion Out of Islam Among Celebrities in Indonesia - Budiawan Budiawan (IKAT: The Indonesian Journal of Southeast Asian Studies, 2020)
In Muslim-majority Indonesia religious conversion to Islam among celebrities always makes it a piece of good news. Infotainment programs of most TV channels broadcast it as their prime news. However, the opposite direction, namely the religious conversion out of Islam to other religions, is hardly possible to broadcast in conventional media such as TV, newspaper, radio, etc.  It is a very sensitive issue, which could cause a mass outcry. Yet, such a phenomenon is easily found in a new media platform, such as YouTube. This paper explores the netizens’ responses to religious conversion out of Islam to Christianity among Indonesian celebrities. By scrutinizing this phenomenon, this paper aims to show to what extent new media provides a space for the religious minorities to speak for themselves. By closely reading their comments, this paper finds that in new media being a religious minority does not matter to represent themselves.